NaHS or Lovastatin Attenuates Cyclosporine A–Induced Hypertension in Rats by Inhibiting Epithelial Sodium Channels - Wang, Qiu-Shi; Liang, Chen; Jiang, Shuai; Zhu, Di; Sun, Yu; Niu, Na; Yang, Xu; Yang, Yan-Chao; Dong, Bi-Han; Yao, Jie; Yu, Chang-Jiang; Lou, Jie; et al. (Frontiers in Pharmacology, 2021)
The use of cyclosporine A (CsA) in transplant recipients is limited due to its side effects of causing severe hypertension. We have previously shown that CsA increases the activity of the epithelial sodium channel (ENaC) in cultured distal nephron cells. However, it remains unknown whether ENaC mediates CsA-induced hypertension and how we could prevent hypertension. Our data show that the open probability of ENaC in principal cells of split-open cortical collecting ducts was significantly increased after treatment of rats with CsA; the increase was attenuated by lovastatin. Moreover, CsA also elevated the levels of intracellular cholesterol (Cho), intracellular reactive oxygen species (ROS) via activation of NADPH oxidase p47phox, serum- and glucocorticoid-induced kinase isoform 1 (Sgk1), and phosphorylated neural precursor cell–expressed developmentally downregulated protein 4–2 (p-Nedd4-2) in the kidney cortex. Lovastatin also abolished CsA-induced elevation of α-, ß-, and γ-ENaC expressions. CsA elevated systolic blood pressure in rats; the elevation was completely reversed by lovastatin (an inhibitor of cholesterol synthesis), NaHS (a donor of H2S which ameliorated CsA-induced elevation of reactive oxygen species), or amiloride (a potent ENaC blocker). These results suggest that CsA elevates blood pressure by increasing ENaC activity via a signaling cascade associated with elevation of intracellular ROS, activation of Sgk1, and inactivation of Nedd4-2 in an intracellular cholesterol-dependent manner. Our data also show that NaHS ameliorates CsA-induced hypertension by inhibition of oxidative stress.